The structural and sedimentological evolution of the Lagonegro zone, Southern Italy - Wood, A; Wood, Andrew William (1979)
The Lagonegro Zone comprises three structural units which outcrop within the pile of decollement nappes forming the southern Italian Appenines. Stratigraphic, structural and sedimentological evidence suggests that the zone represents the relics of a Mesozoic basin that developed amidst the carbonate platforms bordering the southern margin of Tethys. Mapping has confirmed that the Lagonegro I, Lagonegro II and Monte Foraporta Units are separated by thrusts and are stacked in ascending order. Middle Triassic fine-grained terrigenous clastic sediments and neritic limestone olistoliths of Lagonegro Unit II record the disintegration of a young carbonate platform under the influence of extensional tectonics. Deposition and redeposition of hemi-pelagic lime-mud washed from the adjacent shallow-water platforms during the Late Triassic is manifested in both Lagonegro units by the cherty limestones of the Sirino Formation; a gradual transition from calcareous to siliceous deposition at the top of the formation reflects the subsidence of the basin-floor beneath the Calcite Compensation Depth. Contrasting patterns of siliceous and calciclastic sedimentation developed during the Jurassic, probably imposed by renewed extensional tectonics; coeval calciclastic deposition in a small, and at times anoxic marginal basin is recorded in the Monte Foraporta Unit. Dolomitisation of basinal carbonate rocks took place during the Jurassic due to mixing of saline pore-fluids with meteoric water recharged from the adjacent carbonate platforms. Deposition of terrigenous shales below the Calcite Compensation Depth occurred during the Lower Cretaceous, but calcareous sedimentation was resumed in the Late Cretaceous and Palaeogene. The progressive deepening of the basin documented by these facies transitions is attributed to regional subsidence, caused by crustal extension and attenuation, and relative accretion of the surrounding platforms; comparable basal stratigraphies in several ophiolitic zones of the Alpine-Mediterranean region suggest that many Tethyan 'oceanic' basins may have initially developed in a similar manner.